Entero-atmospheric fistula migration: a new management alternative for complex septic open abdomen - Pereira, Bruno; Duchesne, Juan; Concon-Filho, Admar; Leppäniemi, Ari (Anestezjologia Intensywna Terapia, 2020)
The open abdomen technique is a surgical strategy used in life-threatening conditions. After recognizing the morbidity and mortality attributed to abdominal compartment syndrome (ACS), several methods were developed to avoid this complication. The primary goal of temporary abdominal closure (TAC) is to create a tension-free closure of the abdomen without increasing intra-abdominal pressure. The optimal method of TAC should contain and protect the contents of the peritoneal cavity from external contamination and injury, preserve fascia; minimize desiccation and damage to viscera, remove and quantify third space fluid; prevent loss of domain, lower bacterial count, inflammatory response, keep the patient’s abdominal wall skin dry and intact; preserve the integrity of the abdominal wall, be simple to perform and maintain, provide ease of reentry and have minimal adverse physiologic effects. Negative pressure wound therapy allowed the TAC method to achieve these objectives, but the presence of enteric fistulas or entero-atmospheric fistulas is still a challenge for even the most experienced surgeon. Here we describe two new alternatives to manage the septic complex abdomen with entero-atmospheric fistula.